Protected Area Management - Sladonja, Barbara (IntechOpen, 2012)
Protected areas are at the base of the most national and international conservation strategies. Due to the many unpredictable elements in ecology matters, each protected area requires a case-specific set of guidelines but a common issue is how to cope with human interaction. The management of protected areas is replete with challenges and the only way to gain understanding and achieve greater management possibilities is to exchange experiences and knowledge. Environmental managers are aware of that and together with scientists are looking for more modern and better solutions, both with respect to natural resources and human interactions in many issues regarding nature protection. This publication presents reviews and research results on protected areas management, as well as 12 case studies derived from around the world with the aim of improving management effectiveness of the protected areas.